Pelvic Pyomyositis in Childhood: Clinical and Radiological Findings in a Tertiary Pediatric Center - Giulia Abbati; Sarah Abu Rumeileh; Anna Perrone; Luisa Galli; Massimo Resti; Sandra Trapani (MDPI AG, 2022)
Pyomyositis (PM) is an infrequent but increasing bacterial infection of the skeletal muscle, with muscles of the pelvis and thigh frequently involved. The diagnosis is often challenging, especially when a deep muscle is affected. We present a single-center pediatric cohort affected by pelvic PM. A retrospective analysis was performed, including children admitted to Meyer Children's Hospital between 2010 and 2020. Demographic, anamnestic, clinical, laboratory, radiological and management data were collected. Forty-seven patients (range 8 days-16.5 years, 66% males) were selected. Pain (64%), functional limitations (40%) and fever (38%) were the most common presenting symptoms; 11% developed sepsis. The median time to reach the diagnosis was 5 days (IQR 3-9). Staphylococcus aureus was the most common organism (30%), Methicillin-Resistant S aureus (MRSA) in 14%. PM was associated with osteomyelitis (17%), arthritis (19%) or both (45%). The infection was multifocal in 87% of children and determined abscesses in 44% (40% multiple). Pelvic MRI scan, including diffusion-weighted imaging (DWI), always showed abnormalities when performed. Clinical and laboratory findings in pelvic PM are unspecific, especially in infancy. Nevertheless, the infection may be severe, and the suspicion should be higher. MRI is the most useful radiological technique, and DWI sequence could reveal insidious infections.